Carbonation and utilization of basic oxygen furnace slag coupled with concentrated water from electrodeionization. (May 2018) - Li, Yemei; Pei, Silu; Pan, Shu-Yuan; Chiang, Pen-Chi; Lu, Changyi; Ouyang, Tong
Graphical abstract: Highlights: The integrated triphase waste treatment in industry is feasible. High level of Ca 2+ and pH hindered Ca 2+ leaching from BOFS. The surface coverage model described the carbonation of BOFS in CW-EDI well. The suggested substitution ratio for carbonated BOFS in cement mortar was 10%. Abstract: In this study, the integrated recycle process of basic oxygen furnace slag (BOFS) coupled with concentrated water from electrodeionization (CW-EDI) which was introduced into the direct carbonation process for the first time was investigated. The effects of different operating parameters on carbonation conversions of BOFS were studied and the reaction kinetics were determined via surface coverage model. Meanwhile, the changes of CW-EDI during leaching and carbonation processes were measured. Furthermore, the performance evaluation of BOFS applied as supplementary cementitious materials (SCMs) and a cost and benefits analysis of the whole process was conducted. The results indicated the feasibility of the integrated system to industrial solid waste, sewage, and exhaust treatments and the maximum achievable carbonation conversion of BOFS was approximately 60.9% with R 2 of 0.958–0.982. A high level of calcium ion and the alkaline solution hindered the leaching of calcium ion from BOFS, whereas sodium ion was absorbed by BOFS simultaneously. The properties of the cement that used BOFS as SCMs met ASTM requirements. The suggested substitution ratios for fresh and carbonated BOFS in cement mortars were 15% and 10%, respectively. The economic results revealed the superiority of the carbonation and utilization process over traditional treatments in CO2 emission reduction, cost saving and profit gaining.